Rhizosphere fungal community, soil physicochemical properties, understorey vegetation and their relationship during post-coal mining reclamation in East Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sudrajat, Widhayasa B, Rusdiansyah, Susanto D. 2019. Rhizosphere fungal community, soil physicochemical properties, understorey vegetation and their relationship during post-coal mining reclamation in East Kalimantan, Indonesia. Biodiversitas 20: 1953-1962.  The objective of this study was to evaluate the composition of fungal community in rhizosphere, understorey vegetation and soil physicochemical properties post-coal mining reclamation. Soil sampling was conducted using a series of reclamation stages plots (undisturbed, disturbed, two, nine, twelves and sixteen years of reclamation) with drill ground at a depth of 0-30 cm. On each plot, five-point drilling was conducted; soil samples were composited; and their physicochemical properties including soil pH, organic carbon, total N, available P, available K, Ca, Mg, Fe, Mn, and S content were analyzed. Rhizosphere microfungi were isolated by using serial dilution and plated on potato dextrose agar added with Streptomycin. Identification and characterization of soil microfungi were done with the help of accessible manuals of fungi. The results showed that fungal genera at rhizosphere during post-coal mining reclamation were Aspergillus, Penicillium, Cephalosporium, Gliocladium, Humicola, Trichoderma, and Paecilomyces. Aspergillus was dominant comprising 74% of the total isolates. The fungal density in the undisturbed soil and the post-coal mining reclamation soil were higher than in the disturbed soil. The fungal rhizosphere groups isolated were saprophytic fungi that were present in a high relative density. In addition, the results showed that fungal rhizosphere was negatively correlated with soil pH and organic carbon. On the other hand, fungal rhizosphere was positively correlated with total N, available P, and available K. It can be concluded that the time period of post-coal mining reclamation, vegetation, and soil physicochemical profoundly determined the soil fungal community.
Keywords: microfungal rhizosphere, post-coal mining reclamation, soil physicochemical